Web-Based Design of Drug Supply Stock at the Selotong Village Sub-district Health Center, Secanggang District, Langkat Regency - Lia Riyanti; Muhammad Donni Lesmana Siahaan; Darmeli Nasution (Bahasa Indonesia, 2026)
The Sub-District Health Center (Pustu) plays a crucial role in supporting public health services, particularly in the provision of medicines. However, drug stock management at the Sub-District Health Center in Selotong Village, Secanggang District, Langkat Regency, is still performed manually, resulting in various problems such as inaccurate stock data, delayed recording, and difficulties in preparing reports. This study aims to design and build a web-based drug stock information system to improve the effectiveness and efficiency of drug data management. The system development method used is the Waterfall Model, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The system was developed using the PHP programming language and MySQL database. The system's main features include drug data management, recording incoming and outgoing drugs, real-time stock monitoring, and automatic report generation. The results of the study indicate that the system is able to minimize recording errors, increase data accuracy, and facilitate officers in managing drug stocks. Thus, this system is expected to improve the quality of health services at the Sub-District Health Center in Selotong Village.